Development of a Scale Measuring Discursive Responsible Leadership - Voegtlin, Christian (Journal of business ethics, 2011)
The paper advances the conceptual understanding of responsible leadership and develops an empirical scale of discursive responsible leadership. The concept of responsible leadership presented here draws on deliberative practices and discursive conflict resolution, combining the macro-view of the business firm as a political actor with the micro-view of leadership. Ideal responsible leadership conduct thereby goes beyond the dyadic leader–follower interaction to include all stakeholders. The paper offers a definition and operationalization of responsible leadership. The studies that have been conducted to develop the discursive responsible leadership scale validated the scale, discriminated it from other leadership scales, and demonstrated its utility in affecting unethical behavior and job satisfaction in organizations. Responsible leadership is shown to be first, dependent on the hierarchical level in an organization; second, capable of reducing unethical treatment of employees; and finally, a means of enhancing the job satisfaction of employees. The paper concludes with study limitations, future research directions and practical implications.